Pengaruh Inisiasi Menyusui Dini Terhadap Perubahan Suhu Tubuh Bayi Baru Lahir - Kurniyati, Eka Meiri; Sarti, Siti; Irawati, Bety (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2021)
Early Breastfeeding Initiation (IMD) has been shown to be able to reduce neonatal mortality. Babies who are given the opportunity to breastfeed within the first hour and allow skin-to-skin contact between the baby and mother, can reduce 22% of infant mortality in the first 28 days. This study aims to determine the effect of early initiation of breastfeeding (IMD) on changes in body temperature in newborns. This type of research is a Quasi Experiment with a pretest and posttest approach. Total population of all newborns in Lombang village. The sampling technique used random sampling technique, the sample size obtained 40 respondents. Univariate and bivariate data analysis used the T test. The mean before Early Initiation of Breastfeeding (IMD) was 0.42 and after Early Initiation of Breastfeeding (IMD) was 0.15. The results of data analysis using a paired sample test obtained a significancy of 0.001 so that there is an effect of Early Breastfeeding Initiation (IMD) on changes in body temperature in newborns (p value < 0.05). Early Breastfeeding Initiation (IMD) has been shown to be able to reduce neonatal mortality. Babies who are given the opportunity to breastfeed within the first hour and allow skin-to-skin contact between the baby and mother, can reduce 22% of the first day.